History of Water Supply and Governance in Kenya (1895-2005) Lessons and Futures - Nyanchaga, Ezekiel Nyangeri (Tampere University Press, 2016)
This book on the History of Water Development in Kenya transverses through a matrix of infrastructural development, administration, policy, legal and legislation framework, and evolution of various water supply technologies in an inimitably comprehensive approach. The book has carefully constructed the development over one century timeline of water supply and provided the future prediction of the services. The book is a quest to track and understand the origin, the development and sustainability of water supplies within 100 years of its 1st water supply constructed by the railways as the pioneer of water supply in Kenya. It interrogates how the water legislations, policies and administration came to be and what the drivers of water supplies were, when the 1st water reforms mounted and the status of the reform implementation. It elucidates on the role of development partners in influencing the choice of technology, policy and legislative framework. Preparation of this book took fifteen years of passionate research from Kenya National Archives; Kenya Railways; Ministry of Water Development; Colonial archival materials at Rhodes House, Oxford, UK; and the British Institute in Eastern Africa. The research findings have been disseminated in several peer reviewed journals; and several presentations in local, regional and international conferences. Eng Ezekiel Nyangeri Nyanchaga is an Associate Professor, Department of Civil and Construction Engineering, University of Nairobi, Doctor of Technology holder in Civil Engineering, Tampere University of Technology, Finland. Professor Nyangeri is a licensed and practicing consulting engineer with over 35 years of professional experience and over 28 years of academic teaching experience at the University of Nairobi, Kenya.